Internet and Social Media Coverage of Women’s Football in Poland: A Qualitative Critical Discourse Analysis - Magdalena ZMUDA PALKA; Alex C. GANG (Communications of International Proceedings, 2023)
Poland is a country where women's football is just entering the traditional media. Most information about women’s football can be found on internet and various social media platforms. This article examines internet and social media coverage of women’s football, wherein it first identifies online sources that draw most attention from the public to analyze their contents to identify concepts that define contemporary women’s football in Poland. An in-depth analysis on online contents and comments left by the users has revealed themes, such as discrimination against female footballers and inequality between men’s and women’s football, all of which are enabled, if not encouraged, by the practice of hegemonic masculinity that is pervasive in the current Polish society.
Keywords: Critical Discourse Analysis; Hegemonic Masculinity; Social Media; Qualitative; Women’s Football